How are the built environment and household travel characteristics associated with children's active transport in Melbourne, Australia?. (March 2019) - Carver, A.; Barr, A.; Singh, A.; Badland, H.; Mavoa, S.; Bentley, R.
Abstract: Background: Children's active transport (AT) is a potential source of habitual physical activity with established health benefits. We aimed to examine built environment and household travel characteristics as predictors of AT to school and total daily duration of physical activity accumulated via AT. Methods: Cross-sectional household travel survey data from 713 households with children aged 5–12 years (n = 1024) residing < 2 km from school (i.e. walking distance) across Melbourne, Australia (2012–16) were combined with objectively-measured distance to school and walkability (based on intersection density, housing density, land use mix) around home and school. Multilevel multivariable modified-Poisson regression analyses examined built environment variables (distance to school, walkability, traffic) and household travel behaviours (children's and adults' trip chaining, adult accompaniment to school) as predictors of: (1) AT to school; (2) total daily duration of AT of ≥  20 min; adjusted for spatial clustering (at SA1 level) and household variables (income, employment, cars, bicycles). Results: Most children (80%) had adult accompaniment to school but only 28% walked/cycled with an adult. Overall, 39% of children used AT to school and 24% accrued ≥ 20 min of AT-related physical activity. AT to school was positively associated with higher (rather than lower) walkability around home and school, direct travel (not trip chaining) and residing close to school (< 0.75 km rather than ≥ 1.25 km), and negatively associated with adult accompaniment and longer distance travelled onward in adult trip chains. AT of ≥ 20 min duration daily was positively associated with higher walkability around school, direct travel to/from school; and negatively associated with adult accompaniment to, and distance trip chained onward from, school. Conclusions: To increase AT to school it is worth investing in infrastructure designed to improve walkability around schools, coupled with campaigns that target whole households to promote age-appropriate independent mobility rather than adult accompaniment, which tends to involve children being driven. Highlights: Walkable school environments promote AT throughout the day, not just to school. Pedestrian infrastructure should be combined with promotion of AT to households. Household travel survey data were combined with objective built environment data. Trip-chaining by parents and children was related to less active transport (AT). Adult accompaniment was associated with motorised rather than active transport.